2014
DOI: 10.2147/ccide.s53209
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive veneers: current state of the art

Abstract: Ceramic veneers are considered a conservative solution for patients requiring improvement of the shape, color, or position of their anterior teeth. Ceramic veneers have been extensively and successfully used to mask intrinsic staining, to give the appearance of straightening, and to correct minor malformations of anterior teeth without the removal of substantial amounts of sound tooth substance. The current literature was reviewed to search for the most important parameters determining the long-term success an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…8 It has been suggested that a maximum of 0.5 mm thickness to be done at the cervical region of labial veneer preparation. 9 In order to standardize our preparation design three wheels depth cutter was used to have minimum depth cutting. Then, silicon index was performed for checking final preparation depth and design.…”
Section: Discussionmentioning
confidence: 99%
“…8 It has been suggested that a maximum of 0.5 mm thickness to be done at the cervical region of labial veneer preparation. 9 In order to standardize our preparation design three wheels depth cutter was used to have minimum depth cutting. Then, silicon index was performed for checking final preparation depth and design.…”
Section: Discussionmentioning
confidence: 99%
“…There are several methods to obtain the necessary reduction as the free hand, which is the use of grooves and silicone guides that allow a visualization of the reduction needed to reach the shape and contours of the preplanned shape [8, 13]. Different models of tooth preparation have been described, differing only in the incisal third, overlap (palatine chamfer), and incisal reduction with the elimination of the palatine chamfer, resulting in stronger restorations and preparation of the simplified tooth [2, 3, 5]. Regarding the use of the best preparation, there is a disagreement among the authors, as some believe that the palatine chamfer is necessary to reinforce the ceramic veneer, since studies of the clinical behavior of this preparation showed results with greater resistance to fracture when compared to the preparations with 1 mm of incisal reduction with top joint or nonincisal preparation [12].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, procedures are accomplished with minimal wear of the dental tissue, maintaining the color stability [1]. The use of the mock-up technique and bonding procedures are very important to achieve excellent results when working with feldspathic ceramic veneers for the restoration of anterior teeth [2].…”
Section: Introductionmentioning
confidence: 99%
“…The great advantages of consolidating membership in the enamel increase the indications of ceramic restorations with minimal or no preparation [24]. The majority of cases restored with laminate veneers do not require tooth preparation but rather enamel recontouring [25].…”
Section: Discussionmentioning
confidence: 99%